(untitled) (The Pakistan Development Review, 2015)
Income inequality is one of the critical barriers to growth and development in most of the developing countries including Pakistan. Every third man in Pakistan falls below the poverty line1. Moreover, the budget deficit has also been a serious issue throughout the history of Pakistan‟s economy. The persistent budget deficit is the constant source of increasing poverty and deterioration of income distribution. Since deficit is financed by increasing indirect taxes and money supply, it causes the reduction in purchasing power and leads the masses towards poverty [Arif and Farooq (2011)]. Therefore, it is a dire need of the economy to have a good public policy such that it could reduce budget deficit, alleviate poverty and redistribute income. Malik and Saqib (1985) suggest that the resources of the economy can be distributed equally only through appropriate changes in the tax system. Fiscal policy can have a significant influence on removing the gap between haves and havenots both directly and indirectly. It directly affects the disposable income of individuals, whereas affecting their future earning capacities indirectly